Revitalisasi Peran Manajemen Kurikulum PAI Dalam Menanggulangi Bahaya Narkolema (Pendekatan Al-Qur’an Hadis Dan Psikologi Sebagai Solusi) - Najihatul Fadhliyah (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2018)
One practical effort that can be made in families and schools is to provide an explanation of religious education early on according to the level of understanding of children, this effort is very important and should be done as a preventive measure. The theoretical implication that can be drawn from this article is that the Qur'an and the Hadith as well as the source of Islamic law, it is also a source of knowledge and solution for all problems in human life. The problem of danger of narcotics that is very threatening to human life, especially children today can be examined and looked for solutions in the Qur'an and Hadith. More than that the content of both can be connected with other scholarship, which in this article al-Qur'an Hadith connect with psychology so that there is a harmonious interconnection between the science of religion with psychology. Thus did not rule out the Qur'an and Hadith as a source of law and Islamic religious knowledge to be connected with other sciences. Hope the author hopefully this article can be a scientific contribution, especially the field of PAI which will always be ready and open to continue to be done multidisciplinary approach so as to produce solutions to various problems in the community.